Development Model of Village Economic Potential Towards Independent Village in the Covid-19 Pandemic - Prince Charles Heston Runtunuwu; Amran Husen; Baster Douglas Kareng (JEJAK: Jurnal Ekonomi dan Kebijakan, 2022)
This study aims to identify the economic potential of the agriculture, plantation, fisheries, tourism, and trade sectors in Central Lolada. This research is a descriptive study using primary data analysis through interviews with all village heads. In order to raise village competitiveness, mapping of local potential needs to identify and explore potential that can be done by the community it self so that it will be appropriate in village development because the village as a government (head and community) clearly understands the potential of both natural resources and available human resources. The results show that the plantation sector is the main commodity produced, while the fishery sector is still very concerned and needs a touch of policy. For the tourism sector, there is only one tourist destination managed by the government. Meanwhile, for the trade sector, it is dominated by household scale industries. The Covid-19 pandemic doesn't really interfere with people's production activities, there is only the trade sector because it's limited by policy.Â